Design of a Radiosonde System for Air Quality Monitoring in the Tangerang City Area - Muhammad Asa Kardora A (Journal of Computation Physics and Earth Science (JoCPES), 2023)
Tangerang City, located in Banten Province, Indonesia, experiences high rainfall levels that often lead to damaging floods. Climate change has exacerbated these disasters with increasingly unpredictable weather extremes. To address these challenges, upper-air observations using radiosondes are crucial for real-time atmospheric monitoring. Radiosondes effectively measure meteorological parameters such as air pressure, temperature, and humidity when flown into the atmosphere by balloons. This study developed a cost-effective and easily implementable radiosonde system to enhance meteorological data collection in Tangerang City. Thus, the system supports accurate weather analysis and improves disaster management and environmental decision-making in the region.